(untitled) (Research, Society and Development, 2023)
Sugarcane is an essential crop in the Brazilian economy. The adoption of techniques in the acclimatization of plants in vitro contributes to success in the field. The present work aims to evaluate the effect of Azospirillum brasilense on the acclimatization of sugarcane seedlings. The experiment was conducted with six treatments and twelve replications. There were two control treatments without inoculation, one with N fertilization and one without, and four with A. brasilense (2.0x108 CFU) at different doses (19.92mL + N fertilization, 9.84mL, 19.92mL, and 39.84mL). Evaluations were seedling height (SH), stem diameter (SD), number of shoots per tube (NS), number of leaves (NL), fresh aerial weight (AFM), root fresh weight (RFM), total chlorophyll (TC), foliar nitrogen (FN) and visual microscopic study of the roots. The results showed that the recommended dose of A. brasilense + N fertilization increased by 36% in seedling height, 29% in stem diameter, 85% in aerial fresh mass, 21% in total chlorophyll, 142% in foliar N, and also increased root hairs and the presence of microbial biofilm. Therefore, the bacterium A. brasilense can be used in association with nitrogen fertilizers or alone, where it obtained great benefits in the increase of biomass.